(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This paper aims to shed new light on the subject of sailors’ mental health issues. Previous studies have been impeded by the difficulty of obtaining enough data on the mental health of international seafarers to allow for cross-sections with other employees and/or time. An alternative approach was taken in this study, which sought to determine whether or not mental illness among seafarers is seen as an important issue by key stakeholders, what factors seafarers identify as supporting or undermining mental health and well-being aboard freighters, as well as what policies and practices ship operators could implement to better support seafarers’ mental health and well-being. It was conducted using a mix of primary data collected via surveys and secondary data collected through interviews and questionnaires delivered by interviewers and semi-structured interviews (known as P&I clubs). According to the findings of the survey, maritime charities, business groups, and trade unions are very concerned about the mental health and well-being of seafarers. Employers, on the other hand, see it as a less urgent issue. Many seafarers and certain companies encourage proactive initiatives to enhance shipboard communication infrastructure and recreational facilities, as well as job circumstances and physical health of seafarers to promote greater onboard mental and emotional well-being. Reactive tactics (e.g., seafarer counselling) and self-help strategies aimed towards seafarers may not be as successful as these measures in enhancing the well-being of crew members.